2021
DOI: 10.1371/journal.ppat.1009684
|View full text |Cite
|
Sign up to set email alerts
|

Tropilaelaps mercedesae parasitism changes behavior and gene expression in honey bee workers

Abstract: Tropilaelaps mercedesae is one of the most problematic honey bee parasites and has become more threatening to the beekeeping industry. Tropilaelaps can easily parasitize immature honey bees (larvae and pupae) and have both lethal and sublethal effects on the individual worker bees. Our study for the first time experimentally assessed the effects of T. mercedesae on olfactory learning, flight ability, homing ability as well as transcriptional changes in parasitized adult honey bees. T. mercedesae infestation ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…An increase in mite infestation rates can be expected where the presence of injuries on honey bees caused by parasitic mites is relatively high because these mites have rapid locomotion and reproductive rates [ 12 , 23 ]. Indeed, a previous study has reported that increased numbers of injuries are positively correlated with increased numbers of actively feeding mites [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…An increase in mite infestation rates can be expected where the presence of injuries on honey bees caused by parasitic mites is relatively high because these mites have rapid locomotion and reproductive rates [ 12 , 23 ]. Indeed, a previous study has reported that increased numbers of injuries are positively correlated with increased numbers of actively feeding mites [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tropilaelaps mite infestations showed a negative effect on the olfactory learning, flight ability, and homing ability of A . mellifera [ 12 ]. Gao et al [ 12 ] reported that mushroom bodies of Tropilaelaps mite-infested honey bees significantly increased when compared with uninfested honey bees, which may be related to a lower learning ability in the infested honey bees.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These mites have co-evolved with their hosts, developing an intimate dependence on honeybees for survival. While Varroa mites primarily parasitize bees in their brood cells [6,13], Euvarroa and Tropilaelaps demonstrate host specificity towards Dwarf honeybees (Apis florea) and giant honeybees (Apis dorsata), respectively [7,[14][15][16][17]. The most pathogenic species within the genus Acarapis primarily parasitize A. mellifera but have also been found in Asian honeybee species [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%